(3MGTjI GddGQj Ydi TQM bGVj ejQ Ydi GdgOGjIs - (3GddGQj GdedJhj GdCfUGQj GdSYOj GdYHGOj, eUdM GdOjf, eMeO Hf UdGM Hf LdGd, J (B979 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj JNdU HgOGjI MceI MhGTj bdhHfG Efj CJjJ ajeG eVi HMhGTj cGTaI Yf ZhGTj Ydi TQM GdgOGjI dHYV ef eJCNQj Cgd GdaVd hGdOQGjI bhdg GYde Cf GdMceI Yde HCMhGd CYjGf GdehLhOGJ s
(3BNQgG (B:s
(3ejd GdMQcI Edi LgGJ eNJdaI EdG ef WHjYI SeGhjI aj Gdcdj eSJOYjI dgG GdMQcI GdGLRGA ef LgI PhGJgG hWHGFYgG bSQjI hMQcI Gdcd HGYJHGQ GdWHjYI GdfhYjI GdJj dg WHjYI hbO jfJbV s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 196s
(3cTa GdXfhf (B2 / 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs